The Effect of Internal Marketing of Islamic Banks in Palembang City on The Quality of Customer Service With Job Satisfaction as a Mediator - Setyadi, Bakti; Helmi, Sulaiman; Mohamad, Syed Ismail Syed (IKONOMIKA, 2022)
This study aims to see how the role of job satisfaction as a mediator on the influence of internal marketing on the quality of customer service at Islamic Banks in Palembang City. This study uses a quantitative approach to conduct a descriptive survey. A cross-sectional survey is used in this study. The research sample consisted of 135 respondents, 45 staff, and 90 customers from 9 Islamic Banks in Palembang City surveyed using a structured questionnaire. Data were analyzed using Partial Least Square Structural Equation Modeling (SEM-PLS). The study's findings indicate that internal marketing significantly impacts the quality of services provided to Islamic bank customers.Furthermore, job satisfaction appears to be an essential mediating role in improving the quality of service provided to customers of Islamic Bank. The study's uniqueness is that the developed model met the criteria for the suitability of various approaches, implying that using internal marketing to train employees can improve customer service quality. Islamic banks will be more widely accepted in the community if they use internal marketing strategies and job satisfaction as a mediator in improving service quality.